Understanding the Neural Correlates of Increasing Cognitive Demand During Dual-Task Walking in Older Adults - Salzman, Talia (Université d'Ottawa / University of Ottawa, 2020)
Introduction: The prefrontal cortex (PFC) is highly susceptible to age-related deterioration. As such, executive function deficits are commonly observed when older adults process two attention-demanding tasks simultaneously. Everyday tasks such as walking and talking on the phone involve executive functions and the integration of cognitive-motor pathways. However, less is known about this relationship as cognitive demands increase. Methods: Twenty healthy older adults (M = 71.8 years, SD = 6.4) performed four auditory cognitive tasks of increasing demand, including a simple reaction time (SRT), go/no-go (GNG), n-back (NBK), and double number sequence (DNS) task with or without self-paced walking (i.e., single- versus dual-task). Using a blocked design, prefrontal hemodynamic changes (i.e., oxy- [∆HbO2] and deoxyhemoglobin [∆HbR]) were measured using functional near-infrared spectroscopy (fNIRS) and performance was assessed using measures of response time (s), accuracy (% correct) and gait speed (m/s). Results: Prefrontal activation decreased between the single- and dual-tasks across all task demands. Behaviourally, the SRT response times were significantly faster than GNG and NBK. Accuracy decreased between single- and dual-tasks and with increasing demand, but the NBK and DNS tasks were not significantly different. An interaction between task and demand was observed for gait speed such that the DNS dual-task was significantly slower than the single-task. Conclusion: Neural findings support an automatic locomotor control strategy in that cerebral oxygenation decreased between single- and dual-tasks and gait speed was maintained up until the most demanding cognitive task. However, decreased prefrontal activation was inefficient at supporting response time and accuracy performance which may indicate that cognitive performance is differentially affected by cognitive demand and deficits in executive functioning.
Keywords: fNIRS; Dual-task; Gait; Cognitive aging